Investigating subjectivity : classical and new perspectives - Heiden, Gerrit Jan van der, 1976- (Studies in Contemporary Phenomenology, 2012)
The notion of subjectivity is one of the most fundamental notions for modern philosophy that only gains in importance in present-day discussions. This volume gathers essays from both young and senior researchers that examine which role subjectivity plays in both classical and contemporary phenomenology. The essays discuss the importance of a phenomenological account of subjectivity for the nature and the status of phenomenology but they also discuss how the phenomenological account of the subject offers new perspectives on themes from practical philosophy and from the philosophy of mind. Thus, this volume does not only show how multifaceted the question of subjectivity is but also how important this theme continues to be for present-day philosophy.